2013
DOI: 10.1074/jbc.m113.520288
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous Activation of Transient Receptor Potential Vanilloid 1 (TRPV1) Channels by Negatively Charged Intracellular Lipids

Abstract: Background: Regulation of TRPV1 by phosphoinositides is controversial. Results: ATP reactivates TRPV1 after run-down in excised inside-out patches by generating phosphoinositides; many other negatively charged lipids may also support TRPV1 activity. Conclusion: Despite its promiscuous activation, phosphoinositides are the key endogenous cofactors for TRPV1 activity. Significance: Our data may reconcile discordant data obtained in different experimental settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 55 publications
6
94
0
Order By: Relevance
“…either short-chain, long-chain, or natural PI(4,5)P 2 to the intracellular leaflet of excised patches or to one side of a planar bilayer containing reconstituted TRPV1 potentiates activation of TRPV1 (6,12,31). Application of purified, recombinant pleckstrin homology domain protein from phospholipase C␦1, a PI(4,5)P 2 -selective binding protein, to inside-out excised patches inhibits the capsaicin-activated current (11).…”
Section: Discussionmentioning
confidence: 99%
“…either short-chain, long-chain, or natural PI(4,5)P 2 to the intracellular leaflet of excised patches or to one side of a planar bilayer containing reconstituted TRPV1 potentiates activation of TRPV1 (6,12,31). Application of purified, recombinant pleckstrin homology domain protein from phospholipase C␦1, a PI(4,5)P 2 -selective binding protein, to inside-out excised patches inhibits the capsaicin-activated current (11).…”
Section: Discussionmentioning
confidence: 99%
“…5), the eicosanoids HPETE [12-(S)-5-hydroperoxyeicosatetraenoic acid], 15-(S)-HPETE, 5-(S)-hydroxyeicosatetraenoic acid, 20-hydroxyeicosatetraenoic acid, leukotriene B4 (LTB4), N-arachidonoyldopamine (NADA), N-oleoyldopamine, and polyamines (reviewed in Morales-Lázaro et al, 2013). Negatively charged intracellular lipids can also activate TRPV1 (Lukacs et al, 2013). Generally speaking, TRPV1 activation by these compounds requires such high concentrations that are unlikely to occur under physiologic conditions.…”
Section: +mentioning
confidence: 99%
“…PI(4,5)P 2 has been proposed to inhibit TRPV1, mediating the sensitizing actions of bradykinin and nerve growth factor (Chuang et al, 2001;Cao et al, 2013a). In contrast, others (including us) have proposed that PI(4,5)P 2 activates TRPV1 (Stein et al, 2006;Lukacs et al, 2007Lukacs et al, , 2013aKlein et al, 2008), and the depletion of PI(4,5)P 2 by phospholipase C may play a role in Ca 2+ -dependent desensitization (Mercado et al, 2010;Lukacs et al, 2013b). However, a recent study measured the apparent affinity of TRPV1 for diC8-PI(4,5)P 2 and found that the activating effects occurred with a K 1/2 of only 0.03 mol % in the plasma membrane, raising the question of whether PI(4,5)P 2 levels in the plasma membrane ever get sufficiently low selectivity must involve multiple, specific inter actions between TRPV1 and the phosphoinositide ligand.…”
Section: Discussionmentioning
confidence: 97%
“…The crystal structure of GIRK2 bound to PI(4,5)P 2 shows a structured binding pocket in which several hydrogen bonds are formed between basic residues in the protein and both the 4 and 5 phosphates (Whorton and MacKinnon, 2011). Based on this structure, it seems reasonable to predict that GIRK2 might display some phosphoinositide Mechanism for phosphoinositide selectivity and activation of TRPV1 ion channels the response of pain receptor neurons to noxious stimuli, disagreement about whether PI(4,5)P 2 activates or inhibits TRPV1 continues (Chuang et al, 2001;Prescott and Julius, 2003;Stein et al, 2006;Lukacs et al, 2007Lukacs et al, , 2013a; Ufret-Vincenty et al, 2011;Cao et al, 2013a,b;Senning et al, 2014). There is also disagreement about whether PI(4,5)P 2 interacts directly with TRPV1 or acts via the integral membrane protein Pirt (Kim et al, 2008;Ufret-Vincenty et al, 2011).…”
mentioning
confidence: 99%